Sensitivity of LPGs in PCFs Fabricated by an Electric Arc to Temperature, Strain, and External Refractive Index - Petrovic, Jovana S.; Dobb, Helen L.; Mezentsev, Vladimir K.; Kalli, Kyriacos; Webb, David J.; Bennion, Ian (My University, 2007)
Sensing properties of long-period gratings (LPGs) fabricated in photonic crystal fibers by an electric arc are explained and quantified by semianalytical and numerical models. In particular, the grating's insensitivity to temperature and simultaneous sensitivity to strain and refractive index are simulated. The modeling procedure is generalized so that it can be applied to a wide range of LPGs in various fibers
Keywords: Optical fibers; Photonic crystals